Advances in small extracellular vesicles: roles in the tumor microenvironment and epithelial ovarian cancer diagnosis and treatment - Peng, Liang; Lai, Yi; Cao, Baodi (Frontiers in Oncology, 2025)
Epithelial ovarian cancer (EOC), one of the most prevalent subtypes of ovarian cancer, has a 5-year survival rate of less than 30%, highlighting the urgent need for novel diagnostic and therapeutic strategies. The tumor microenvironment (TME), a critical regulator of tumor progression, includes various components, among which small extracellular vesicles (sEVs) serve as important molecular carriers, having gained attention as significant contributors to cancer biology. These vesicles, released by cells into the extracellular space, are pivotal in the pathogenesis of EOC. In addition, sEVs show significant promise as biomarkers and therapeutic agents for the treatment and management of this malignancy. This review explores recent advancements in the understanding of sEVs within the TME and their potential applications in the diagnosis and treatment of EOC.